Boron-incorporated Sulfonated polysulfone/polyphosphoric acid electrolytes for supercapacitor application. Issue 2 (3rd April 2019) - Cevik, Emre; Günday, Seyda T.; Yusuf, Abdulmalik; Almessiere, Munirah A.; Bozkurt, Ayhan
ABSTRACT: In the present work, boron-doped multicomponent gel polymer electrolytes composed of host polymer, sulfonated polysulfone (SPSU) and the additives; ionic liquid, 1-ethyl-3-methyl-imidazolium tetrafluoroborate (IL), H3 BO3, polyphosphoric acid (PPA) were prepared. Fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA) techniques were used to characterize the sulfonated polysulfone-based electrolytes. Ion conductivity of these gel electrolytes were studied by dielectric impedance analyzer within the temperature from −20 to 100°C. The ionic conductivity of the SPSU-5IL-1PPA and SPSU-5IL-1H3 BO3 -1PPA were measured as 4.8 × 10 −3 and 9 × 10 −4 S cm −1, respectively. Supercapacitor having activated carbon-based composite electrode and electrolyte was constructed with the configuration: Al/C/electrolyte/C/Al. The electrochemical properties and ion transfer characteristics of the supercapacitor were investigated by the cyclic voltammetry (CV). Galvanostatic charge—discharge experiments exhibited good electrochemical reversibility and produced a specific capacitance value of 120 F g −1 at 1 A g −1 . The symmetric supercapacitor system was retained almost 85% of its initial activity after 1000 cycle.